Aesthetic definitions of the harmonic smile (Research, Society and Development, 2022)
The physical appearance of teeth is a frequent concern of patients and directly influences interpersonal and psychological behavior. An aesthetically healthy smile has the ability to convey feelings and emotions, and patients who have some kind of problem with their smile tend to withdraw and generally have low self-esteem. For dentists, smile aesthetics involves the development of treatments that solve specific problems. Thus, the objective was to carry out an exploratory literature review on the definitions of harmonious smiles based on the principles of Dentistry, with the idea of ​​searching for the perfect smile and comparing it with the natural physiological aspects of each individual. For the elaboration of the research, a review of the narrative literature was carried out considering the dental anatomy, the analyzed ones, the beliefs that involve the types of smile and the social and psychological contributions of a harmonious smile. The bibliographical survey included studies published in Google Academic, Scielo, PubMed and Capes Research Platform databases. The studies included in this research met the criteria of: complete publication and free access. Studies were excluded due to presenting outdated or incomplete information. The result of the research shows that aesthetic harmony is extremely important, because an attractive smile makes the patient more sociable and accepted in their circles. Several factors seemed to make the appearance of the perfect smile, among which were highlighted: gingival characteristics, chroma, opalescence, fluorescence, translucency, brightness, gender and age of patients.